Optimization of Human Umbilical Cord Mesenchymal Stem Cell Cryopreservation Protocol - Palii, Ilona; Redko, Olesia; Lechachenko, Sofiia; Dovhaliuk, Bohdana Anna (Problems of Cryobiology and Cryomedicine, 2024)
Probl Cryobiol Cryomed 2024; 34(4):307